Association of a locus on chromosome 17 with earlier age at onset of cognitive impairment in a familial Amish dataset. (December 2021) - Scott, William K.; Ramos, Jairo; Slifer, Susan H.; Caywood, Laura J.; Prough, Michael B.; Clouse, Jason E.; Dorfsman, Daniel A.; Herington, Sharlene D.; Fuzzell, M. Denise; Fuzzell, Sarada L.; Sewell, Jane L.; Miller, Sherri D.; et al.
Abstract: Background: Studies of cognitive impairment (CI) in Amish communities have identified sibships containing multiple CI and cognitively normal (CN; unaffected after age 75) individuals. We hypothesize that these CN individuals may carry protective alleles delaying age at onset (AAO) of CI, preserving cognition in older age despite increased genetic risk. We conducted a genome‐wide study (GWAS) to identify loci associated with AAO of CI in these individuals. Method: 1, 522 individuals aged 43‐99 (mean age 73.1, 42% men) screened at least once for CI using the modified mini‐mental status exam (3MS) were genotyped using Illumina chipsets. Genotypes were imputed for 7, 815, 951 single nucleotide variant (SNV) with minor allele frequency (MAF) > 1%. The outcome studied was age, defined as 1) age at the first 3MS result indicating impairment (AAO; 3MS <87; 362 CI individuals) or 2) age at last normal exam (3MS >=87, 1, 160 CN individuals). Cox mixed‐effects models examined association between age and each SNV, adjusting for sex, population structure, and familial relationships. To replicate genome‐wide significant findings, SNVs in a 1 Megabase region centered on the peak SNV were examined for association with age using these same methods in the NIA‐LOAD family study dataset (1, 785 AD cases, 1, 565 controls, mean age 73.5; Kunkle et al., 2019). Result: Three SNV were significantly associated (p<5 x 10 ‐8 ) with AAO in the Amish, on chromosomes 6 (rs146729640; Hazard Ratio (HR)=6.38), 9 (rs534551495; HR=2.82), and 17 (rs14538074; HR=3.35). Each region found the common allele associated with later AAO. Replication analysis detected association at rs146729640 on chromosome 17, with nominal statistical significance (HR=1.49, p=0.02). Conclusion: The replicated genome‐wide significant association with AAO on chromosome 17 implicates the SHISA6 gene, which is involved in post‐synaptic transmission in the hippocampus. GWAS studies have not reported association in this region with AD risk or AOO, suggesting this might be a novel locus influencing onset of cognitive impairment, and highlights the power of using unique populations.